FILM DRAMATURGY OF THE MONOLOGUE "PENYAMUN": PERSPECTIVES ON MUSIC, SEMIOTICS, AND ACTING - Tri Laksono, Yunanto; Pramono, Koko Hari; Sabri, Indar (Acintya, 2025)
Monologue based cinema presents distinct challenges in building narrative and dramatic tension, especially in the absence of verbal interaction between characters often the primary force driving a story. Penyamun serves as a compelling case study of how a complete and emotionally resonant cinematic narrative can emerge despite such limitations. The film centers on the existential struggle of a solitary individual in isolation, where internal conflict becomes the core of the drama. Through symbolic and atmospheric techniques, the film replaces conventional dialogue with layered visual metaphors and sonic textures. This study uses a descriptive qualitative method to analyze how music, visual/verbal signs, and acting strategies collaborate to construct meaning. Music functions as an emotional conduit, expressing the protagonist’s psychological shifts and inner turmoil. Visual and verbal signs are examined through a semiotic lens to reveal how layered meanings are constructed and communicated. The actor’s internal and physical performance becomes essential in generating dramatic dynamics and evoking empathy. Findings show that music, semiotic elements, and performance interact synergistically, forming a cohesive dramaturgical structure. These elements do not operate in isolation but reinforce each other to create emotional depth and narrative clarity. Penyamun thus exemplifies a new aesthetic in monologic cinema, demonstrating that powerful cinematic expression can emerge not through dialogue, but through the symbolic and emotional intensity of carefully orchestrated artistic components.